2018
DOI: 10.3126/nepjoph.v9i2.19257
|View full text |Cite
|
Sign up to set email alerts
|

Tacrolimus versus Cyclosporine- Comparative Evaluation as First line drug in Vernal keratoconjuctivitis

Abstract: Introduction: The aim of the study was to evaluate and compare the efficacy, side effects and recurrence rate of vernal kerato conjunctivitis (VKC) with 0.03% tacrolimus and 0.05% cyclosporin. Material and method: A prospective randomised double blinded comparative study was conducted at a tertiary eye center. 46 Patients of VKC between March 2015-August 2015 were randomly divided into two groups and treated for 6weeks with either Tacrolimus(0.03%) eye ointment BD or Cyclosporine (0.05%) eyedrops QID.The main … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(43 citation statements)
references
References 2 publications
1
42
0
Order By: Relevance
“…It has been noted that all the patients have received treatment throughout the study period because of lower concentration of the medication used with negligible adverse effects resulting and good response. It has also been observed that patients on treatment with tacrolimus eye ointment 0.03% did not require any additional medications, which showed its potential role as steroid sparing agent which is in concurrence with the study done by Kumar S et al [7] In this study, both the drugs (cyclosporine eye drops 0.05% and tacrolimus eye ointment 0.03%) were almost equally efficacious (97% and 100% respectively) in treating VKC and did not show any significant difference between their ~ 32 ~ efficacy, which concurs with a similar prospective double masked, randomized comparative study done by Kumari R et al in 2016 in which tacrolimus eye ointment 0.03% brought about an improvement of the signs and symptoms of VKC similar to cyclosporine eye drops [12] . Also, there were no ocular side effects in either group which is in concordance with the study done by Singla E et al [13] IOP, lens and fundus of all the patients were with in normal limits throughout the study period in both groups, which concurs with studies done by Kumari R et al and Singla E et al [12][13] The results of this study are in concurrence with another prospective double-masked, randomized, comparative study conducted in 2016 by Kumari R and Saha CB in which 19 patients received tacrolimus eye ointment 0.03% daily for 6 weeks and another 15 received cyclosporine eye drops 0.5% four times daily for 6 weeks, where it was found that tacrolimus brought about an improvement of the signs and symptoms of VKC similar to that of cyclosporine A [12] .…”
Section: Discussionsupporting
confidence: 91%
“…It has been noted that all the patients have received treatment throughout the study period because of lower concentration of the medication used with negligible adverse effects resulting and good response. It has also been observed that patients on treatment with tacrolimus eye ointment 0.03% did not require any additional medications, which showed its potential role as steroid sparing agent which is in concurrence with the study done by Kumar S et al [7] In this study, both the drugs (cyclosporine eye drops 0.05% and tacrolimus eye ointment 0.03%) were almost equally efficacious (97% and 100% respectively) in treating VKC and did not show any significant difference between their ~ 32 ~ efficacy, which concurs with a similar prospective double masked, randomized comparative study done by Kumari R et al in 2016 in which tacrolimus eye ointment 0.03% brought about an improvement of the signs and symptoms of VKC similar to cyclosporine eye drops [12] . Also, there were no ocular side effects in either group which is in concordance with the study done by Singla E et al [13] IOP, lens and fundus of all the patients were with in normal limits throughout the study period in both groups, which concurs with studies done by Kumari R et al and Singla E et al [12][13] The results of this study are in concurrence with another prospective double-masked, randomized, comparative study conducted in 2016 by Kumari R and Saha CB in which 19 patients received tacrolimus eye ointment 0.03% daily for 6 weeks and another 15 received cyclosporine eye drops 0.5% four times daily for 6 weeks, where it was found that tacrolimus brought about an improvement of the signs and symptoms of VKC similar to that of cyclosporine A [12] .…”
Section: Discussionsupporting
confidence: 91%
“…Five articles were eventually included after the screening based on the established inclusion and exclusion criteria. [12][13][14][15][16] Figure 1 shows the flow chart of literature screening from this meta-analysis.…”
Section: Search Resultsmentioning
confidence: 99%
“…3The TAC treatment duration varied across different studies as well. For instance, one study treated the patients with TAC for up to 6 weeks, 15 while another study treated the patients for just 1 week. 16 (4) The baseline scores of objective signs and baseline scores of subjective symptoms between the five included studies were also different.…”
Section: Systematic Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…In our study both 0.1% Tacrolimus and 2% Cyclosporine cause a reduction in TSSS from 4 th week onwards. A similar prospective, double-masked, randomized comparative study was conducted by Rashmi kumara et al (33) in 2016 in which 19 patients received 0.03%Tacrolimus eye ointment daily for 6 weeks and other 15 recieved 0.05% Cyclosporine eye drops four times daily for 6 weeks. This study reported that tacrolimus brought about an improvement of the signs and symptoms of VKC similar to that of cyclosporine A.…”
Section: Discussionmentioning
confidence: 96%